Knowledge, attitude, practice, and barriers among physicians in the Middle East and North Africa region toward influenza vaccination for the high-risk group of patients: a cross-sectional study - Saadi M. Saleh; Alaa Aljamala; Dina Hafez; Mosab Abu Shqeer; Islam Abukandil; Weam Aldiban; Azza Baraka; DARS Consortium (Tropical Diseases, Travel Medicine and Vaccines)
Abstract Background The influenza vaccine is a cost-effective measure to reduce morbidity and mortality, especially for high-risk patients. Healthcare providers have an essential role in patients’ education about vaccines. This study aims to examine physicians' understanding, perceptions, and practices regarding influenza vaccination in the Middle East and North Africa (MENA) region for high-risk patients. Methods We conducted a multinational cross-sectional study in 21 countries in MENA region from July 10th to September 10th, 2023. Data were collected using an online self-administered survey distributed through different social media platforms. We used a valid questionnaire designed to determine the knowledge, attitude, and practice of physicians toward influenza vaccination. A multivariable binomial logistic regression analysis was conducted to identify significant predictors for offering the influenza vaccine. Results In this study, which involved 2017 physicians (the mean (SD) age was 29 (± 6.2); 52% were males), the majority expressed a low to medium level of knowledge about influenza vaccination, with only 4% displaying a high level of knowledge. Regarding attitude, the majority (n = 1511, 74.9%) were quite concerned. However, only (n = 509, 25.4%) offered the vaccine to patients. The main predictors for offering the vaccine were age (adjusted odd ratio (AOR) = 1.036, 95%CI = 1.003–1.07, p = 0.031), male sex (AOR = 1.39, 95%CI = 1.09–1.77, p = 0.007), living in upper-middle-income countries (AOR = 3.14, 95%CI = 2.1–4.7, p < 0.001), having PhD degree (AOR = 3.15, 95%CI = 1.47–6.71, p = 0.003), being a senior resident (AOR = 2.005, 95%CI = 1.147–3.5, p = 0.015), working two to five shifts per week (AOR = 1.55, 95%CI = 1.02–2.35, p = 0.04), working more than five shifts per week (AOR = 1.75, 95%CI = 1.06- 2.88, p = 0.027), attitude (AOR = 1.33, 95%CI = 1.243- 1.44, p < 0.001), following these practices regarding influenz vaccination with the other office staff: Encourage and offer (AOR = 5.73, 95%CI = 4.11- 8.007, p < 0.001), require but do not offer (AOR = 3.73, 95%CI = 2.59- 5.38, p < 0.001), and require and offer the influenza vaccine (AOR = 6.79, 95%CI = 4.88- 9.45, p < 0.001) to the office staff. The main barriers to influenza vaccination were unawareness of vaccine availability (32%), cost (25%), and forgetfulness (23.4%). Conclusions Approximately half of the physicians were knowledgeable about the flu vaccine, but practice was deficient and impeded by barriers like unawareness and forgetfulness.